2019
DOI: 10.1186/s13195-019-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

A single-nuclei RNA sequencing study of Mendelian and sporadic AD in the human brain

Abstract: Background Alzheimer’s disease (AD) is the most common form of dementia. This neurodegenerative disorder is associated with neuronal death and gliosis heavily impacting the cerebral cortex. AD has a substantial but heterogeneous genetic component, presenting both Mendelian and complex genetic architectures. Using bulk RNA-seq from the parietal lobes and deconvolution methods, we previously reported that brains exhibiting different AD genetic architecture exhibit different cellular proportions. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 38 publications
(45 reference statements)
7
77
0
Order By: Relevance
“…Therefore, future work in postmortem brain could make use of additional markers such as P2RY12 and TMEM119 (homeostatic microglia) [ 4 ], and TREM2 (DAM) to better understand the role of microglia in PD. Future work could also utilise comprehensive genome-wide expression analyses which have become possible through the use of protocols to isolate microglia from human brain tissue [ 58 ] or by singe-cell RNA sequencing using bulk tissue, as has recently been done in Alzheimer’s disease postmortem brain [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future work in postmortem brain could make use of additional markers such as P2RY12 and TMEM119 (homeostatic microglia) [ 4 ], and TREM2 (DAM) to better understand the role of microglia in PD. Future work could also utilise comprehensive genome-wide expression analyses which have become possible through the use of protocols to isolate microglia from human brain tissue [ 58 ] or by singe-cell RNA sequencing using bulk tissue, as has recently been done in Alzheimer’s disease postmortem brain [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The single cell level response due to the alteration of the oral microbiome in the presence of alcohol can provide insight into the continuous cellular response and mechanism that may lead to the permeability of BBB and eventually AD 59 . This technique has been used to study the effects of LPS in neuroinflammatory responses and also 2 different AD studies [60][61][62] . By using scRNA-seq, the distinct types of neurons, glial cells and microglia can be precisely identified by this change 61 .…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been used to study the effects of LPS in neuroinflammatory responses and also 2 different AD studies [60][61][62] . By using scRNA-seq, the distinct types of neurons, glial cells and microglia can be precisely identified by this change 61 . This method can also be used to further profile the diversity of the oral cavity as seen in the study done on the effects of koumiss on the oral microbiome 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, long-read sequencing (e.g., Oxford Nanopore Technology) enables the detection of structural variants [ 116 ], short tandem repeats (STR) [ 117 ], and variable number of tandem repeats (VNTRs) [ 118 ]. High-throughput RNA sequencing (RNA-seq) transcriptomics (e.g., single-cell and single-nuclei RNA-seq) can identify expression signatures potentially associated with disease pathology, providing important insights into potential subpopulations of cells directly involved in disease [ 119 ]. A study showed that the brain of carriers of rare pathogenic APP , PSEN1 , or PSEN2 mutations presented with lower neuron and higher astrocyte relative proportions compared to sporadic AD patients [ 120 ].…”
Section: The Potential Of Additional Omics Tools To Provide Insights mentioning
confidence: 99%